Effect Analysis Of Financing Activities Cash Flows Of The Company. Case Studies On The PT. Indosat, Tbk And PT. Telekomunikasi Indonesia, Tbk. - Soelehan, Aan (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Financing activities is a method that companies use to get money to pay for those needs. Because of the size and potential funding activities in determining the success or failure of the company, the company must be careful in the acquisition and management of financial resources. Broadly speaking, to consider the cash flows from financing activities was added and the reduction of long-term debt and equity, and dividend payments. Debt interest payments and dividend receipts into the cash flow from operating activities. And if the company obtained financing activities run smoothly it will affect the companys cash flow. The purpose of this study is to determine the condition of the financing activities and PT.Telekomunikasi PT.Indosat Tbk Indonesia Tbk: To determine the condition of cash flow in and PT.Telekomunikasi PT.Indosat Tbk Indonesia Tbk: To determine the effect of financing activities on cash flow at PT. Indosat Tbk and PT.Telekomunikasi Indonesia Tbk. The results of the analysis of the funding activity was measured by using the Price Earning Ratio (PER) at PT. Indosat, Tbk has an average value of 27.4616, while the Price Earning Ratio (PER) at PT. Telekomunikasi Indonesia Tbk has an average value which is much better for 14.9339. Debt Ratio at PT. Indosat, Tbk has an average value of 0.6330, while the Debt Ratio at PT. Telekomunikasi Indonesia Tbk has an average value that is not better at 0.4736. Debt to Equity Ratio (DER) at PT. Indosat, Tbk has an average value of 1.1451, while the Debt to Equity Ratio (DER) at PT. Telekomunikasi Indonesia Tbk has an average value that is not better at 0.5274. The analysis of cash flow at PT. Indosat, Tbk produces an average value of cash flows amounting to Rp. -418 675 166 667 in the span of years 2006-2011. Meanwhile, for the cash flow at PT. Telekomunikasi Indonesia, Tbk nilar average yield better cash flow amounting to Rp. 678 112 833 333 in the range of 2006-2011 when compared with PT. Indosat, Tbk. The existence and effect relationships are illustrated in financing activities through the Price Earning Ratio, Debt Ratio, Debt To Equity Ratio and cash flow of PT. Indosat, Tbk can be proven by statistical analysis with each of the correlation value of 10.1%, 6.2%, 21.5%, which means it has a weak and has a significance level respectively by 84.9%, 90 , 7%, and 68.2% greater than the critical value (confidence level) of 10% which means not significant. At PT. Telekomunikasi Indonesia, Tbk, which suggests that the relationship and the effect of financing activities which are described by Price Earning Ratio, Debt Ratio, and Debt To Equity Ratio of the companys cash flow with each correlation value 73.2%, 12.7%, and 11 % which means only the Price Earning Ratio which has a strong relationship and the rest have a weak link, and each has a significance level of 9.8%, 81%, 83.5%, only the Price Earning Ratio is less than critical value (confidence level) of 10% which means a significant, and the remainder is greater than the critical value (confidence level) of 10% which means not significant. Evaluation results of this study suggest that in order for PT. Indosat, Tbk and PT. Telekomunikasi Indonesia, Tbk may increase the funding available for other activities can be run properly, so the cash flow the company will be better.